Pengaruh Disiplin Belajar terhadap Hasil Belajar Bahasa Indonesia - Durrah Mawaddah Siregar; Edi Syaputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Learning discipline is very influential on student learning outcomes. This study aims to determine the determination of school culture, learning discipline and achievement motivation on student learning achievement in Indonesian. Tutoring activities are very influential on the results of learning Indonesian in high grade elementary school. Tutoring can be used as a benchmark for learning success for elementary school students. Meanwhile, Indonesian language learning outcomes can be influenced by several factors, including internal factors and students' external factors. This study focuses on tutoring that affects students' Indonesian learning outcomes. So that students tend not to like Indonesian subjects and this can affect student learning outcomes. This research is an ex post facto research, because there is no control over the independent variables and the researcher does not regulate or manipulate the independent variables. This research consists of two variables, namely one independent variable and one dependent variable. The independent variable in this study is learning discipline (X). While the dependent variable is the result of learning Indonesian (Y). For sampling using saturated sampling technique.